Efficacy and Safety Comparison among Rigid Gas Permeable Contact Lens Correction for Keratoconus - Valenchia Valenchia; Tri Rahayu (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: Rigid gas-permeable contact lenses (RGP CL) are commonly used to manage moderate tosevere keratoconus. The range of RGP CL type currently available for the successful optical correctionof keratoconus has greatly expanded. We compared the efficacy and safety of available RGP CL basedon visual acuity (VA), keratometry, comfort score, and adverse event.Methods: Literature search on RGP CL and keratoconus retrieved 37 citations from 2010-2015. Ninearticles were selected as relevant to our purpose.Results: All studies showed improvement of VA following RGP CL wearing. Greatest improvementwas seen in Rose K CL (.5 - .36) in naÃ¯ve CL patient and Twinbel bevel toric in refitting CL patient(.22). All studies reported lower mean Î”K post fitting RGP CL than pre-fitting. Greatest difference ofmean Î”K pre and post-fitting was observed in YK lens (.72). The most comfortable lens was Rose K(91.5%) followed by Soper CL (87.9%) and Twinbel bevel toric (64.4%). Punctuate corneal stainingfound in a considerable amount with YK lens patient.Conclusion: Among 5 types of RGP CL available now for keratoconus, Rose K provided greatestBCVA improvement in naÃ¯ve CL patient whereas Twinbel bevel toric in refitting patient. YK lensgave greater changes in keratometry post-fitting RGP CL. The most comfortable lens for patient isRose K lens. The most common adverse event of CL wear is punctuate corneal staining in YK lenspatient.Keywords: rigid gas permeable contact lens, keratoconus